(untitled) (Academic Journal of Internal Affairs, 2012)
The bursting of the Tarpa dam in the Tisza basin, was one of the largest natural disasters of the last century in Hungary. Highlighting the most important modifications of the new Disaster Management Law that came into force on the 1st January 2012, and reflecting on the 10th anniversary of the flood, the author recalls the chronicle of the events, the organization of defence activities, and experiences on rebuilding and resettling.